2008
DOI: 10.1093/hmg/ddn187
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH1 mutations in individuals with left ventricular outflow tract malformations reduce ligand-induced signaling

Abstract: Congenital aortic valve stenosis (AVS), coarctation of the aorta (COA) and hypoplastic left heart syndrome (HLHS) are congenital cardiovascular malformations that all involve the left ventricular outflow tract (LVOT). They are presumably caused by a similar developmental mechanism involving the developing endothelium. The exact etiology for most LVOT malformations is unknown, but a strong genetic component has been established. We demonstrate here that mutations in the gene NOTCH1, coding for a receptor in a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
168
0
12

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(191 citation statements)
references
References 29 publications
11
168
0
12
Order By: Relevance
“…The most common malformation associated with CoA is BAov. Autopsy examinations showed 54%-85% of patients with CoA have a BAov [13]. The coexistence of BAov and CoA is important to consider, because it places the patient at a higher risk of aortic complications.…”
Section: Associated Cardiac and Extracardiac Lesionsmentioning
confidence: 99%
“…The most common malformation associated with CoA is BAov. Autopsy examinations showed 54%-85% of patients with CoA have a BAov [13]. The coexistence of BAov and CoA is important to consider, because it places the patient at a higher risk of aortic complications.…”
Section: Associated Cardiac and Extracardiac Lesionsmentioning
confidence: 99%
“…Furthermore, mutations in NOTCH2 and the Notch ligand JAGGED1 are responsible for Alagille syndrome, which is characterized by pulmonary stenosis, ventricular septal defects, coarctation of the aorta, and tetralogy of Fallot, among other developmental defects 16, 17. Notch1 is expressed in the endothelial cells lining the cardiac OFT during development, and mutations in NOTCH1 have been linked primarily to human BAV and other left‐sided cardiac malformations 18, 19. Although these studies indicate the important role for Notch signaling in the development of the cardiac OFT and aortic valve, the underlying mechanisms and the cell lineages in which Notch1 is required have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In a smaller unrelated family, a NOTCH1 frameshift mutation segregated with a similar aortic valve phenotype. Observations of missense NOTCH1 mutations in a subset (~5 %) of individuals with BAV have also been reported with supporting functional data indicating impaired Notch signaling [7,8]. These publications suggested that NOTCH1 haploinsufficiency was a cause of BAV in humans.…”
Section: Notch1 Mutations and Aortic Valve Diseasementioning
confidence: 61%